Massage Effleurage Menggunakan VCO (Virgin Coconut Oil) Pada Pasien Dengan CVA (Cerebro Vaskuler Accident) Dengan Resiko Gangguan Integritas Kulit - Sundari, Erlina; Ismoyowati, Tri Wahyuni (I Care Jurnal Keperawatan STIKes Panti Rapih, 2024)
Background: Weakness in limbs/immobilization in stroke patients with prolonged bed rest poses a risk of skin integrity issues, such as pressure ulcers or decubitus. One intervention that can be performed is skin integrity care using effleurage massage techniques with Virgin Coconut Oil (VCO). Objective: To analyze the intervention of skin integrity care with effleurage massage using VCO on patients with Hemorrhagic Stroke (CVA) at the Bethesda Hospital Yogyakarta in 2023, who are at risk of skin integrity disturbances. Case Management: Patient Ms. Ng, 91 years old, with Hemorrhagic Stroke, was found to have less elastic, wrinkled skin, with redness in bony areas (both heels), sacrum, and back (due to pressure), and scaly, dry, and peeling soles. The patient was immobilized/bedridden. The nursing problem identified was the risk of impaired skin integrity. The nursing plan provided was effleurage massage using VCO. Discussion: After administering skin integrity care with effleurage massage using VCO, as measured by the Braden Scale, the skin integrity score decreased from 9 (high risk) to 14 (moderate risk). Conclusion: The effleurage massage technique with VCO is effective in reducing the risk of impaired skin integrity. Recommendation: This research is expected to provide additional references and knowledge for nursing care of patients with Hemorrhagic Stroke and issues related to skin integrity risk, particularly with the intervention of effleurage massage using VCO. Keywords: VCO (Virgin Coconut Oil) - Effleurage Massage - Risk of Impaired Skin Integrity - CVA (Cerebrovascular Accident)